The Safety and Efficacy of Novel Agents Targeting Factors XI and XII in Early Phase Human Trials - DeLoughery, Emma P.; Olson, Sven R.; Puy, Cristina; McCarty, Owen J. T.; Shatzel, Joseph J. (Seminars in Thrombosis and Hemostasis, 2019)
Although anticoagulation without hemorrhage is a primary aim, this vision has remained as yet out of reach. Even despite the superior safety profile of the direct oral anticoagulants, hemorrhage remains a major risk of anticoagulation. Selective inhibition of the contact pathway of coagulation, specifically coagulation factor XI (FXI) and/or factor XII (FXII), has now substantial epidemiologic and preclinical data supporting the notion that these factors contribute to pathologic thrombosis and are yet primarily dispensable for in vivo hemostasis. In this way, targeting FXI and FXII may revolutionize the future anticoagulation landscape. Several drugs are under development for this purpose, including: ISIS 416858, a FXI antisense oligonucleotide which impairs hepatic synthesis of FXI; MAA868, a monoclonal antibody that binds the procoagulant enzymatic site of both zymogen and activated FXI (FXIa); BAY 1213790, a monoclonal antibody that binds the procoagulant enzymatic site of FXIa only; and AB023, a monoclonal antibody that inhibits activated FXII-mediated activation of FXI, along with two small molecules in clinical trials. Each of these drugs have demonstrated favorable safety profiles in their phases 1 and 2 studies to date, with preclinical data also supporting efficacy of abrogating thrombosis in various animal models. Other benefits of some of these drugs include once-monthly dosing and safety in patients with renal or hepatic impairment, while others offer quickly metabolized parenteral options, thus providing more convenient and widely available anticoagulation options. Though still far from the marketplace, drugs targeting FXI and FXII have the potential to usher in a new era of anticoagulation therapy.
Keywords: thrombosis; factor XI; factor XII; contact pathway; sepsis; hemostasis